Public Perception Analysis of Digital Population Identity Policy in Pontianak City Using Technology Acceptance Model (TAM) Approach - Riyoldi Riyoldi; Entang Adhy Muhtar; Nina Karlina (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze public awareness, perception, and acceptance of the implementation of the Digital Population Identity (DIC) policy in Pontianak City. Using a theoretical framework that integrates the technology acceptance model (TAM), the theory of risk and negative consequences, and the theory of organizational trust, this study explores factors such as usefulness, ease of use, user experience, social influence, facilitating conditions, awareness, perception, and public acceptance of DIC. A questionnaire-based survey was applied to the Pontianak City community selected through a stratified random sampling method. Data analysis was carried out using descriptive and inferential statistics to identify relationships between variables and evaluate factors that influence DIC adoption. The findings of this study are expected to provide relevant information for policymakers to develop strategies for implementing more adaptive and inclusive DIC policies. In addition, this study also identifies local challenges in implementing DIC, including data security and technology access, which can be a basis for developing digital policies in the future.